Photomineralization of organic carbon in a eutrophic, semiarid estuary. Issue 3 (28th January 2020) - Wang, Hongjie; Hu, Xinping; Wetz, Michael S.; Hayes, Kenneth C.; Lu, Kaijun
Abstract: The effect of photomineralization on the carbon cycle in a eutrophic, semiarid estuary (Baffin Bay, Texas) was investigated using closed‐system incubations. Photochemical production rate of dissolved inorganic carbon ranged from 0.16 to 0.68 μ M hr −1, with a daily removal of 0.3∼1.5% of the standing stock of dissolved organic carbon (DOC). The photomineralization rate was negatively correlated with chlorophyll a concentration, suggesting that plankton‐derived DOC was less photoreactive to solar radiation. The stable carbon isotope composition (δ 13 C∼ −18.6‰) of degraded DOC, as calculated using the DIC "Keeling" plot, further indicated high photochemical lability of 13 C‐enriched DOC in this semiarid environment. Our finding showed that photomineralization of 13 C‐enriched DOC is an important component of carbon cycle in this system, and this process does not necessarily remove 13 C‐depleted organic carbon as observed in other coastal systems.